Influence of the emotion of fear on patterns of consumer behavior toward dietary supplements during the COVID-19 pandemic - Dijana Vuković; Boris Jurič; Iva Krnjak (Journal of Risk and Financial Management, 2022)
The focus of this paper is placed on the role of emotions in consumer behavior, specifically in the process of purchasing dietary supplements during the COVID-19 pandemic. The theoretical part is based on current knowledge from relevant Croatian and foreign scientific and professional literature on dietary supplements, the COVID-19 pandemic, consumer behavior, decision-making and the impact of emotions on it, while the empirical research portion of this paper details the attitudes of consumers who buy food supplements, the role and importance of different emotions that have a greater or a lesser impact on the purchase of food supplements, with special reference to the timing of the COVID-19 pandemic, and the factors that make consumers decide to purchase food supplements. This research was conducted in the form of a survey that included 257 respondents who were actual users of dietary supplements. It showed that the main drive for buying dietary supplements during the COVID-19 pandemic is the emotion of fear, as the consumers perceived this new disease as a threat to their health and life.
Keywords: 650; behavioral economics; consumer behavior; COVID-19 pandemic; dietary supplements; emotions